2018
DOI: 10.5604/01.3001.0012.0932
|View full text |Cite
|
Sign up to set email alerts
|

Undue Elevation of Procalcitonin in Pediatric Paracetamol Intoxication is Not Explained by Liver Cell Injury Alone

Abstract: The underlying mechanism is neither caused by infection nor fully explained by liver cell death alone and remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
3
3
0
3
Order By: Relevance
“…In a pediatric cohort study, Tschiedel et al. observed that paracetamol intoxication led to a marked increase in PCT serum levels, correlating with ALT but not correlating with the INR or paracetamol blood levels, consistent with our findings 33 …”
Section: Discussionsupporting
confidence: 92%
“…In a pediatric cohort study, Tschiedel et al. observed that paracetamol intoxication led to a marked increase in PCT serum levels, correlating with ALT but not correlating with the INR or paracetamol blood levels, consistent with our findings 33 …”
Section: Discussionsupporting
confidence: 92%
“…Recientemente Tschiedel y cols. [7] han propuesto dos posibles mecanismos para explicar el aumento de procalcitonina en la intoxicación por paracetamol. El primero sería la propia hepatoxicidad inducida por el fármaco, que causaría la secreción de ciertas citoquinas, como la interleuquina 2 o el factor de necrosis tumoral alfa, que se comportarían como mediadores para la elevación de la concentración de procalcitonina.…”
Section: Discussionunclassified
“…Tschiedel y cols. [7] han sugerido la implicación en el incremento de procalcitonina asociado a la intoxicación por paracetamol de otros órganos como la célula endotelial a través de la producción de NAPQI.…”
Section: Intervalo De Referenciaunclassified
See 1 more Smart Citation
“…Therefore, anaphylactic shock was strongly suspected. It is possible that the non-infectious pathway of procalcitonin increased due to increased oxidative stress after the administration of acetaminophen for hepatic injury caused by DIC [20][21][22].…”
Section: Discussionmentioning
confidence: 99%